An efficient gene disruption system for the nematophagous fungus Purpureocillium lavendulum. Issue 4 (April 2019) - Liu, Lu; Cao, Yan-Ru; Zhang, Chen-Chen; Fan, Hai-Feng; Guo, Zhi-Yi; Yang, He-Yu; Chen, Mi; Han, Jing-Jing; Xu, Jianping; Zhang, Ke-Qin; Liang, Lian-Ming
Abstract: The fungus Purpureocillium lavendulum (formally Paecilomyces lilacinus ) is a natural enemy of insects and plant-parasitic nematodes, and has been used as an important bio-control agent against agricultural pests all over the world. In order to understand the genetic mechanisms governing its biocontrol efficiency and other biological processes, an effective gene disruption system is needed. Here we report the development of an efficient system which integrates selective markers that differ from Purpureocillium lilacinum, a one-step construction method for gene knockout plasmids, and a ku80 knockout strain for efficient homologous recombination. With this system, we effectively disrupted the transcription factors in the central regulation pathway of sporulation and a serine protease which were contributed to nematode infection, demonstrating this system as an efficient gene disrupting system for further characterization of genes involved in the development and pathogenesis of this fungus. Highlights: Conidia of P. lavendulum can infect and kill C. elegans from the intestinal tract. A high-efficient gene disruption system were developed for P. lavendulum. Deletion of PlKu80 increased gene disruption efficiency in P. lavendulum. PlBrlA have relative low recombination rate despite of length of homolog arms. Deletion of PlPr1D decreased virulence of P. lavendulum when infecting nematodes.